IMPLEMENTASI WIRAUSAHA SOSIAL PADA SEKTOR PERTANIAN SAAT MASA PANDEMI COVID-19 DI KABUPATEN BANDUNG (STUDI KASUS: BUDIDAYA JAMUR VILLA MUSHROOM AGRIFARM) - Solihin, Rici (Banking & Management Review, 2021)
The agricultural sector is still the key to boosting economic growth in Indonesia, even in a crisis. Several agricultural business owners have currently transformed their business into a social enterprise based on community empowerment in their local regions. Social entrepreneurship is seen as a determining factor for the agricultural sector to grow consistently even during the Covid-19 pandemic. This research aims to determine how social entrepreneurship is implemented in the agricultural sector during the Covid-19 pandemic in the Bandung area. This study aims to determine and describe the application of social entrepreneurship criteria in the agricultural sector, especially in mushroom cultivation during the Covid-19 pandemic in the Bandung area. This study aims to identify and describe what factors determine the success in applying the criteria of social entrepreneurship. This study uses a descriptive method with a qualitative approach. The results showed that the application of social entrepreneurship in the agricultural sector in the Bandung area had met the five criteria of social entrepreneurship involving social mission, empowerment, ethical business principles, social impact, and business sustainability.